PWE-145 Characterisation Of Circulating And Liver Infiltrating Mait Cells In Human Inflammatory Liver Diseases. (9th June 2014) - Parekh, K; Jeffery, H; Shaw, J; Iqbal, T; Adams, DH; Oo, YH
Abstract : Introduction: Mucosal-Associated Invariant T (MAIT) cells are characterised by expression of the semi-invariant TCR α-chain Vα7.2-Jα33 and high expression of CD161 and shown to play a role at mucosal barriers. They display a limited T cell receptor repertoire being restricted by the MHC class 1-related molecule, MR1 but secrete high levels of pro-inflammatory cytokines suggesting they may play an important role in liver inflammation. We have shown before that the majority of MAIT cells in circulation are CD8 + MAIT cells. Recently, presence of MIAT cells have been described within human liver perfusate. However, very little is known about the phenotype and functions of liver infiltrating MAIT cells. In this study we investigated the frequencies and phenotypes of human liver infiltrating MAIT cells in healthy donors and diseased livers. Methods: Peripheral blood and explanted liver infiltrating lymphocytes were freshly isolated and phenotyped by multicolour flow cytometry. The MAIT population was defined as CD3 + CD16 Hi Va7.2 + . Results: There was no difference in frequencies of circulating CD3 Pos CD161 Hi Va7.2 Pos MAIT cells between patients with inflammatory liver disease and healthy controls (1.4 ± 0.7% vs. 2.3 ± 1.0%) and the majority were CD8 Pos (82.3 ± 3.1%) with a smaller population of CD4 Pos (2.7 ± 0.6%) and double negative CD8 Neg CD4 Neg cells (14.8 ± 2.9%). Total CD3 Pos CD161 Hi Va7.2 Pos MAIT frequencies were not significantly altered in inflamed liver tissue compared to blood (4.4 ± 1.0% vs. 1.4 ± 0.7%). However, in the inflamed liver, the CD8 + subset was reduced (61.2 ± 6.2 vs. 82.3 ± 3.1, P = 0.006) while the CD4 + MAIT subset was increased (15.9 ± 5.6 vs. 2.7 ± 0.6, P = 0.02). CXCR3, liver homing chemokine receptor was highly enriched on circulating and liver infiltrating CD3 Pos CD161 Hi Va7.2 Pos MAIT cells (>75%). Liver infiltrating MAIT cells expressed chemokine receptors CCR5 (78.4 ± 7.2), CX3CR1 (51.3 ± 10), CCR6 (46.3 ± 14.8) and CXCR6 (36 ± 6.2%). Interestingly they expressed high levels of the integrin β7 (39.1 ± 3.6) and CD103 (19.6 ± 5.5%), which are associated with mucosal immune responses. They also expressed the cytokine receptors IL23R (27.1 ± 8.5%) and IL18Rα (76.7 ± 5%). Conclusion: We have described for the first time that CD3 Pos CD161 Hi Va7.2 Pos MAIT cells are present in inflamed human liver and express high levels of CXCR3 receptor implicated in lymphocyte recruitment to the liver and three other chemokine receptors CX3CR1 and CCR6 and CXCR6 that are associated with homing to portal tracts and bile ducts. Thus MAIT cells may play a role in biliary pathology. Disclosure of Interest: None Declared.